Arthurian literature, XVIII - Busby, Keith (Boydell & Brewer, 2001)
Epitomises what is best in Arthurian scholarship today. ZEITSCHRIFT FüR ROMANISCHE PHILOLOGIE. This latest issue of 'Arthurian Literature' continues the tradition of the journal, combining critical studies with editions of primary Arthurian texts. Varied in their linguistic and chronological coverage, the articles deal with major areas of Arthurian studies, from early French romance through late medieval English chronicle to contemporary fiction. Topics include Béroul's 'Tristan', 'Tristan de Nanteuil', the Anglo-Norman 'Brut', and the 'Morte', while an edition of the text of an 'extrait' of Chrétien's 'Erec et Enide' prepared by the eighteenth-century scholar La Curne de Sainte-Palaye offers important insights into both scholarship on Chretien, and our understanding of the Enlightenment. The volume is completed with an encyclopaedic treatment of Arthurian literature, art and film produced between 1995 and 1995, acting as an update to 'The New Arthurian Encyclopedia'. Contributors: RICHARD ILLINGWORTH, JANE TAYLOR, CARLETON CARROLL, MARIA COLOMBO TIMELLI, RALUCA RADULESCU, JULIA MARVIN, NORRIS LACY, RAYMOND THOMPSON.
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Arthur / King; Arthurian romances